Conference – 2015 Equation (3)

j i t = β A i t + θ i + u i t MathType@MTEF@5@5@+= feaagKart1ev2aaatCvAUfeBSjuyZL2yd9gzLbvyNv2CaerbuLwBLn hiov2DGi1BTfMBaeXatLxBI9gBaerbd9wDYLwzYbItLDharqqtubsr 4rNCHbGeaGqiVu0Je9sqqrpepC0xbbL8F4rqqrFfpeea0xe9Lq=Jc9 vqaqpepm0xbba9pwe9Q8fs0=yqaqpepae9pg0FirpepeKkFr0xfr=x fr=xb9adbaqaaeGaciGaaiaabeqaamaabaabaaGcbaGaamOAamaaBa aaleaacaWGPbGaamiDaaqabaGccqGH9aqpcqaHYoGycaWGbbWaaSba aSqaaiaadMgacaWG0baabeaakiabgUcaRiabeI7aXnaaBaaaleaaca WGPbaabeaakiabgUcaRiaadwhadaWgaaWcbaGaamyAaiaadshaaeqa aaaa@4637@